The Colonization of Lifeworlds of Education by Work: Restoration and Recoupling of Lifeworld and System in the Inner Self - Morrison, Keith (Horyzonty Wychowania, 2015)
The argument is raised that, in an age of the networked, connectedsociety in an information-rich environment with communication possibilities as never before experienced or made possible, the displacement of educational virtues of morality, ethics and the development of all-round human beings, by those of money, labour, power and work are speeding apace, and the disconnect between system and lifeworld is increasing. Drawing initially on the work of Habermas, in which the colonization of the lifeworld occurs by system imperatives of rationalization, labour, money and power, the paper argues that such moves are manifested starkly in discourses of the relation between education and work, andfive areas are introduced in which the links operate. The marketization and commodification of education, together with its incorporation into the service of capital and labour, are attested through a short worked example of one small territory within the larger context of China. Then, taking a lead from Sertillanges and Habermas’s later work, the paper argues for: (a) a reaffirmation of the importance of moral, ethical and spiritual dimensions of education; (b) the breaking of a narrowly instrumental, capital-acquisitive view of education as serving the jobs market and social control and towards a liberating view of education as communicative action and the development of being rather than simply behaving; (c) the importance of transcendence and immanence; and, thereby, (d) moves towards the re-integration of system and lifeworld in participating subjects. Podnoszony bywa argument, że w czasach połączonego społeczeństwa sieciowego, w środowisku bogatym w informacje, o niespotykanych nigdy wcześniej możliwościach komunikacyjnych, wychowawcze cnoty związane z moralnością, etyką i całościowym rozwojem człowieka są w coraz większym stopniu zastępowane przez pieniądze, pracę i władzę, co powoduje coraz szybsze poszerzanie się przepaści pomiędzy systemem a światem społecznym. Wychodząc od koncepcji Habermasa, według którego kolonizacja świata społecznego dokonuje się przez systemowe imperatywy racjonalizacji, pracy, pieniędzy i władzy, autor referatu utrzymuje, że takie przesunięcia w jaskrawy sposób przejawiają się w dyskursach dotyczących relacji między edukacją a pracą. Relacjete występują w pięciu obszarach. Urynkowienie i utowarowienie edukacji, wraz z wprzęgnięciem jej w służbę kapitału i pracy, przedstawione zostały na przykładzie jednego małego terytorium w Chinach. Następnie, czerpiąc inspirację z myśli Sertillanges’a i późnego Habermasa, artykuł postuluje: (a) potwierdzenie ważności moralnych, etycznych i duchowych wymiarów kształcenia; (b) odejście od wąsko instrumentalnej, kapitalistyczno-zachłannej wizji edukacji służebnej wobec rynku pracy i kontroli społecznej w stronę wyzwalającego widzenia edukacji jako działania komunikacyjnego i rozwoju bycia, a nie tylko zachowań; (c) ważność transcendencji i immanencji; a przez to (d) działania zmierzające w kierunku reintegracji systemu i świata społecznego uczestniczących w nim podmiotów.